The Role of Electronic Learning Systems to Help Learning Strategies and to Improve Self Motivated Learning: Enhancing Self-Regulated Learning with Electronic Learning Systems (Journal of Advances and Scholarly Researches in Allied Education, 2011)
A course management system (CMS) is a software program or integrated platform thatcontains a series of web-based tools to support a number of activities and course managementprocedures  (Severson, 2004). Examples  of Course Management  Systems are Blackboard,WebCT,  eCollege,  Moodle,  Desire2Learn, Angel, etc.  An argument for  the  adoption  of e- learning environments using CMSs is the flexibility of such environments when reaching out topotential learners in remote areas where brick and mortar institutions are non-existent. It is also believed  that  e-learning  environments  can have  potential  added learning benefits and can improve students‘ and educators‘ self-regulation skills, in particular their metacognitive skills. In spite of this potential to improve learning by means of using a CMS for the delivery of e-learning,  the  features  and functionalities that  have been built into  these  systems are often underutilized. As a consequence, the created learning environments in CMSs do not adequatelyscaffold learners to improve their self- regulation skills. In order to support the improvement of both the learners‘ subject matter knowledge and learning strategy application, the e-learning environments within  CMSs should be  designed  to address learners‘  diversity  in terms of learning styles, prior knowledge, culture, and self-regulation skills. Self-regulative learners are learners who can demonstrate ‗personal  initiative, perseverance and adaptive skill in pursuing learning‘ (Zimmerman, 2002).  Self-regulation requires  adequate  monitoring strategies  and metacognitive skills. The created e-learning environments should encourage the application of learners‘ metacognitive skills by prompting learners to plan, attend to relevant content, and monitor and  evaluate their learning. This  position paper  sets  out  to inform policy  makers,educators, researchers, and others of the importance of a metacognitive e-learning approachwhen designing instruction using Course Management Systems. Such a metacognitive approach will improve the utilization of CMSs to support learners on their path to self-regulation. We argue that a powerful CMS incorporates features and functionalities that can provide extensivescaffolding to learners and support them in becoming self-regulated learners. Finally, we believethat extensive training and  support  is essential  if educators are expected to  develop  and implement CMSs as powerful learning tools.